MANAJEMEN PEMBELAJARAN TERPADU BAGI KECAKAPAN HIDUP TUNAGRAHITA - Mumpuniarti . (LPMPP Universitas Negeri Yogyakarta, 2004)
Mentally retarded children are children whose potentials are more limited than those of the average normal child. These limited potentials need to be developed in order that they can live self-dependentry. The self-dependence can be achieved if they possess life skills. Successful learning of those skills in the mentally retarded can be achieved through the use of, among others, an integrated learning management approach. The approach implies a process of planning, organizing, actuating, and controlling their learning in order that they achieve capability in acquiring some life skills, with the capability to be acquired according to their condition because of their limited potentials. Andthe process integrated with various fields ofstudy and knowledge in solving problems in routine daily life. Such problems require an integrated application of various fields of study and knowledge and the application of the integrated learning management for the mentally retarded can be considered an effort to increase their manpower learning oflife skills can become an indicator that achieving life skills is useful for the life ofthe mentally retarded. Key words: life skills ofthe mentally retarded, integrated learning management.